2020
DOI: 10.4236/jss.2020.89024
|View full text |Cite
|
Sign up to set email alerts
|

School Improvement Specialist Coaches Plus (SISC+) as a Catalyst for Enhancing Teachers Pedagogy Aspect in Malaysia

Abstract: The School Improvement Specialist Coaches Plus (SISC+) programmed in Malaysia has been in operation since 2012 and is a part of the professional education team in all districts in Malaysia that helps teachers through their coaches. According to the District Transformation Programmed 3.0 (DTP 3.0), the role of SISC+ is underpinned by knowledge and skills in curriculum, pedagogy and assessment aspects. The aim of this study was therefore to identify the level of competence of SISC+ in the field of pedagogy. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…To note, the insufficient materials on the new assessment (Ghavifekr, Kunjappan & Ramasamy, 2016) and lack of training (Arumugham, 2020) have been compounded to this problem. Balang Mahamod and Buang (2020) reported that teachers were found to have a limited understanding on enacting CEFR CBA leaving the implementation of this new policy become vague as it did not align to the needs of policymakers. This situation has sparked a contested site to see that even the TPD was conducted for the teachers, however, it does not able to provide insights for them to enact the changes in education claiming that the TPD was ineffective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To note, the insufficient materials on the new assessment (Ghavifekr, Kunjappan & Ramasamy, 2016) and lack of training (Arumugham, 2020) have been compounded to this problem. Balang Mahamod and Buang (2020) reported that teachers were found to have a limited understanding on enacting CEFR CBA leaving the implementation of this new policy become vague as it did not align to the needs of policymakers. This situation has sparked a contested site to see that even the TPD was conducted for the teachers, however, it does not able to provide insights for them to enact the changes in education claiming that the TPD was ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…To note, many past literatures (Arumugham, 2020, Balang et al, 2020, Acarerdol & Yildizli, 2018 has limit the discussion by addressing the effectiveness of TPD in engaging teachers' implementation of CEFR CBA. However, the types of TPD strategies in the enactment of CEFR CBA has yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%